MATEMATIKA DALAM KEUANGAN SYARIAH - Reka Meilani (Budgeting: Jurnal Akuntansi Syariah, 2022)
Mathematical modeling plays a major role in various disciplines. The contribution of mathematical modeling is not only attached to the concepts of general sciences, such as conventional economics and finance, but also includes Islamic sciences, such as Islamic economics and finance. This study aims to reveal the role of mathematics in the development of Islamic economics and finance. This study uses a qualitative approach in the form of library research. The results of the discussion are expressed through the ideas described in two general information, namely: (1) The results of the analysis of mapping studies on mathematical models in Islamic economics and finance, and (2) an explanation of several examples of mathematical models applied in economic theories and Islamic finance. From the results of this study, it was found that the number of publications on the development of mathematical models in Islamic economics and finance research from 1980-2020 experienced a significant increase and also began to have a high impact on other research. In addition, the development of mathematical models in solving Islamic economic and financial problems is also a trend in current research. An example is research on the development of mathematical models on the concept of profit-sharing financing and the concept of zakat.